Docease Simpliyfying Healthcare Navigation Through an Intuitive Appointment Web Solution - Abdirahim, Mohamed Abdiraman; HASAN BASARI , ABD SAMAD (Applied Information Technology And Computer Science, 2025)
The integration of digital technology has substantially enhanced patient care and operational efficiency in healthcare; nonetheless, traditional appointment scheduling continues to be inefficient, characterized by prolonged wait times and ambiguous availability. This research is to create a Doctor Appointment Web System for Pusat Kesihatan Universiti (PKU) at Universiti Tun Hussein Onn Malaysia, emphasizing real-time scheduling, doctor profiles, and user-friendly interfaces. An agile methodology prioritizing iterative development and ongoing testing was adopted to guarantee system stability and adaptability. The results include decreased waiting periods, increased healthcare accessibility, and better patient satisfaction, alongside improved telemedicine and resource distribution. These findings highlight the capacity of digital technologies to enhance healthcare procedures and strengthen patient-provider relationships, with further efforts recommended to incorporate capabilities such as predictive analytics and integration with comprehensive health systems.